Associations between neutrophil percentage to albumin ratio and rheumatoid arthritis versus osteoarthritis: a comprehensive analysis utilizing the NHANES database - Ding, Wenquan; La, Rui; Wang, Shenghao; He, Zhiyuan; Jiang, Dinghua; Zhang, Zhigang; Ni, Hao; Xu, Wu; Huang, Lixin; Wu, Qian (Frontiers in Immunology, 2025)
ObjectivesThe association between the neutrophil percentage to albumin ratio (NPAR) and the risk of osteoarthritis (OA) and rheumatoid arthritis (RA) remains unclear. This study aims to investigate the association between NPAR and the risk of OA and RA.MethodsThis cross-sectional study analyzed data from 92,062 American adults in the NHANES database between 1999 and 2016. Various statistical analyses were conducted to investigate the associations between NPAR and the risks of OA and RA, including multivariable logistic regression, subgroup analysis, smooth curve fitting, and threshold effect analysis.ResultsAfter screening, the final study population included 36,147 participants, with 3,881 individuals diagnosed with OA and 2,178 with RA. After adjusting for confounding factors, higher NPAR levels were associated with an increased risk of RA (OR=1.05; 95% CI: 1.03-1.07; P <0.0001), but not with OA (OR=1.01; 95% CI: 0.99-1.02; P =0.755). This association was remarkably consistent across subgroups by age, sex, body mass index (BMI), alcohol consumption, hypertension, diabetes, and smoking status. Further analyses using curve fitting and threshold effect models revealed a nonlinear association between NPAR and RA, with an inflection point identified at 15.56.ConclusionHigh levels of NPAR is positively associated with the prevalence of RA. This provides us with new insights for the management and treatment of RA patients.